To study maternal mortality and complications leading to maternal death in the tertiary care centre - Garg, Pratibha (International Journal of Medical Research and Review, 2016)
Objective: To study maternal mortality and complications leading to maternal death in the tertiary care centre over the five years of period. Method: A retrospective and prospective study of all maternal deaths from January 2001 to December 2005 was carried out. Results: There were total 204 maternal deaths out of 24,620 live births giving a maternal mortality rate (MMR) of 828.59 per 100,000 live births. Unbooked cases accounted for 74% of maternal deaths. The majority of deaths occurred in 25-29 years age group and 71% were multigravida. Out of 204 maternal deaths 72.06% deaths were due to direct causes. Hemorrhage was the commonest cause of death (36%) followed by toxaemia of pregnancy (19%) and sepsis accounted for 135 of deaths. Conclusion: Hemorrhage, toxaemia of pregnancy and sepsis were found to be direct major cause of death. Anaemia and other indirect causes like jaundice, malaria, heart disease were other indirect causes of deaths.